Simulasi Model Risiko Pekerjaan Perbaikan Tanah Metode Konsolidasi Berbasis Value Engineering - ., Mirnayani; Vidayanti, Desiana; Susanti, Irriene Indah (Fakultas Teknik, Universitas Wiraraja, 2025)
Soft soil with low bearing capacity presents challenges for infrastructure projects like the Kayu Agung–Palembang–Betung Toll Road. This study aims to identify the most efficient soil improvement method using the Value engineering (VE) approach and simulate associated risks. Using a descriptive quantitative method, data were collected through field observations, expert questionnaires, and project documents. Three methods were evaluated: preloading without vertical drains, with vertical drains, and vacuum preloading. Risk simulation was conducted using the Monte Carlo method with Crystal Ball software. Results show that preloading without vertical drains is the most cost-efficient but carries higher technical risks. Preloading with vertical drains offers a good balance between cost and stability, while vacuum preloading ensures optimal stability with higher costs.